Attitude of Under-graduate Nursing Students towards Clinical Duties - A cross sectional study - Amir Sultan, Sheraz Khan, Afrooz Bibi, Haseen Jamal, Safia Rafeeque, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nursing programmes are designed as a combination of theoretical knowledge and clinical practice; therefore, students are introduced to clinical practice step-by-step. The attitude toward the clinical practice of students decides how these students will achieve their clinical objectives and put their theoretical knowledge into practice. Methods: It is a cross-sectional descriptive with a study population of nursing students enrolled in 4-year BSN at any institute of nursing sciences in Khyber Pukhtankhwa. Among the study sample of 330 participants, 21 students with incomplete information were skipped from the study. After testing for validity and reliability, data were collected on a modified questionnaire with yes and no options. Results: Positive attitude of 1st year students was (89%), 2nd years were (84%), 3rd years were (81%), and 4th years were (83%), while the negative attitude of 1st year students was (11%), 2nd year was (16%), 3rd year was (19%), and 4th year was (17%). The overall positive behaviors of the participants were (81%), mean of (257.42) and standard deviation (48.91), while the overall negative behaviors of the participants were (19%), mean of (52) and standard deviation of (48.91). There is evidence from this study that nursing students have a positive attitude toward clinical duties. A good number of students show a negative attitude towards the idea that there should be a change in the clinical setting, while some students report less interaction with the instructor, while some students face difficulty in learning clinical skills and facing patients. Conclusion: There should be changes in clinical settings and good interaction with students in clinical areas to guide skills development and develop boldness to face the patients.